House of Assembly Question and Replies - South Africa Parliament (Cape Town Government Printers, 1974)
South Africa Parliament House of Assembly. Debates of Standing Committees published
Merged with: Debates of the House of Delegates, and; Debates of the House of Representatives, to form: Debates of Parliament. Debates of Standing Committees published annually and parallel with Afrikaans title. 139 v. 22 cm.
Keywords: House of Assembly; Questions and Replies; Fifth Session; Fourth Parliament; 1974; Vol. 48; Index to Questions; ISBN 0621017329; JC045342